Anxiety and L2 self-images: the anxious self - Şimşek, Erdi (2018)
This thesis brings together three studies, beginning with a preliminary qualitative study to survey the scene, and expanding by means of corroboration by an actual survey with a questionnaire, in order to investigate the mechanisms of foreign language anxiety (FLA). Surveying the scene by collecting exploratory qualitative and quantitative data from anxious learners, for gaining new insights from these individuals’ perspectives, provided first the insight and then the necessary evidence that reframing anxiety as the “anxious self” – anxious about what to do in L2 classes or L2 spoken environments, about how others will respond and about the likelihood of taking successful action in L2 when necessary – might offer a useful approach to link anxiety research to other areas of second language acquisition (SLA), where the importance of the self-concept has been recognised, as well as to clinical psychology, which has long employed relaxation, guided-imagery and systematic de-sensitization in shaping the self-concept of the individual. A five-week intervention programme, based on this new approach, was designed with the purpose of reducing learners’ anxiety levels. Using a combination of quantitative and qualitative measures, the impact of the programme on Turkish learners of English was documented, and results indicated that participants showed significantly lower levels of language anxiety, neuroticism, L2 (second language) stage fright, safety-seeking behaviours and quitting tendencies at the end of the programme. The findings also confirmed that visualisation training helped learners to improve their anxious self images, which resulted in increased levels of self-confidence and resilience to anxiety. The employment of relaxation techniques was shown to effectively relieve the somatic symptoms of language anxiety. The use of systematic de-sensitization activities showed positive results over the course of the study, supporting participants’ ability to remain relaxed in anxiety-provoking situations. Co-operation and rapport in the classroom had also improved by the end of the programme and findings confirmed that conceptualising anxiety as a dimension of self could be a productive and effective approach, offering rich pedagogical implications.